PERANAN STATISTIK DALAM BIDANG AKUNTANSI (PENDEKATAN TEKNIK SAMPLING AUDIT OLEH AUDITOR) - Aziz, Abdul; Dimyati, Novika; Wiguna, M. Wisnu Kusuma; Irianto, Bambang Setyobudi (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2023)
This paper explains the role of statistics in the field of accounting, especially the approach to audit sampling techniques by auditors. There are two sample sizes through the application of a statistical and non-statistical based formula. The application of a statistical-based sample size was carried out using a random selection method with the help of the Ms application. Excel (Index Formula, Rand Formula, and Rank Formula) applied to the